Book-Zakat differences and Earnings Persistence: Evidence from Saudi Arabia - Alhadadi, Abdullah (Curtin University, 2021)
This thesis examines the relationship between book-zakat differences (BZDs) and earnings persistence for a sample of Saudi firms. Further, the thesis investigates the impact of two important Saudi's capital market institutional settings: the appointment of royal family directors to the board of directors and institutional investors' presence on earnings persistence. Next, the study investigates whether these two institutional settings mitigate the relationship between BZDs and earnings persistence.